Increased frequency of HLA-B44 in recurrent sinopulmonary infections (RESPI) - Johnston, Douglas T (Clinical immunology (Orlando, Fla.), 2006)
To test whether MHC alleles associated with common variable immune deficiency (CVID) might also be over-represented in patients with normal serum immunoglobulin levels who suffer with recurrent sinopulmonary infections (RESPI), we identified 62 consecutive RESPI patients and compared their HLA-B and HLA-DR antigen frequencies to those of 60 consecutive patients with CVID, 1627 Alabama Caucasian bone marrow donors, and 997,230 published US Caucasians. Either HLA-B44, -B8, -DR3(17), or -DR7 was present in 74% of the RESPI and 85% of the CVID patients. HLA-B44 prevalence in particular proved identical between RESPI and CVID. When compared to US Caucasians, the increased prevalence of the four HLA alleles proved significant at P < 0.0001, P < 0.0001, P = 0.0005, and P = 0.02, respectively. When compared to Alabama Caucasians, only the increased prevalence of HLA-B44 achieved statistical significance (P = 0.0001). Inheritance of HLA-B44 may yield susceptibility to recurrent sinopulmonary infection even in the presence of normal serum immunoglobulin levels